2011
DOI: 10.1144/m35.42
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 42 Greenland petroleum exploration: history, breakthroughs in understanding and future challenges

Abstract: In recent years there has been a growing interest from the industry for exploration in the Arctic and other high-latitude areas, including possible future petroleum provinces in Greenland. Exploration focus in Greenland has mainly been on central west Greenland with several licensing rounds and, as a promising result, the highest number of licences ever seen in Greenland. Activities in the coming years are likely to be directed more towards Baffin Bay and to the NE Greenland shelf. Both of these regions offer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 63 publications
0
9
0
3
Order By: Relevance
“…The US Geological Survey concluded that the North-East Greenland shelf could be an important future petroleum province but stressed that Cenozoic uplift and erosion are important risk factors for the development of the hydrocarbon system (Gautier et al 2011). Christiansen (2011) found uplift to be the main exploration risk in East and North-East Greenland, but he also assigned a significant uncertainty to the limited stratigraphic control due to lack of geophysical and well data. Major oil companies acquired several licences for hydrocarbon exploration off North-East Greenland between 76 and 80°N in 2012 and 2013 (Bojesen-Koefoed et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The US Geological Survey concluded that the North-East Greenland shelf could be an important future petroleum province but stressed that Cenozoic uplift and erosion are important risk factors for the development of the hydrocarbon system (Gautier et al 2011). Christiansen (2011) found uplift to be the main exploration risk in East and North-East Greenland, but he also assigned a significant uncertainty to the limited stratigraphic control due to lack of geophysical and well data. Major oil companies acquired several licences for hydrocarbon exploration off North-East Greenland between 76 and 80°N in 2012 and 2013 (Bojesen-Koefoed et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The very large volumes suggested by Price and Whitham (1997) in their elegantly presented but analytically poorly documented account had a serious impact on the evaluation of the resources in the region, when East Greenland was included in the 2000 World Petroleum Assessment by the United States Geological Survey (USGS). The high numbers, especially on maximum field sizes, created many discussions between industry, GEUS and the USGS (Christiansen, 2011). One interesting outcome was the initiation of the Arctic Petroleum Appraisal by the USGS, where only well-documented data were applied and eventually with more realistic resource numbers as the main consequence (Gautier, 2007;Gautier et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Our datasets from the Barents Sea document extensive oil and methane leakage from hydrocarbon reservoirs that have experienced uplift and glacial erosion, constituting an important source of methane to the water column, and, possibly, atmospheric inventory. Signi cantly, there are numerous analogous geological settings (sedimentary basins with petroleum potential that have experienced uplift and glacial erosion) across North Atlantic and Arctic continental margins where we may expect abundant hydrocarbon leakage: the Timan-Pechora Basin in the Pechora Sea 31 , the Sverdrup Basin on the northern margin of North America 69 , the Eastern Basin in the Russian part of the Barents Sea 45 , the western (Norwegian) part of the Barents Sea 41 , sedimentary basins surrounding British Isles 46,70 and sedimentary basins of western and eastern Greenland 47,71,72 (Fig. 1).…”
Section: Implications For Formerly Glaciated Hydrocarbon-bearing Shelvesmentioning
confidence: 99%